2013
DOI: 10.1007/s00256-013-1649-9
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical properties of the calcaneal tendon in vivo assessed by transient shear wave elastography

Abstract: SWE allows the elastic properties of the calcaneal tendon to be evaluated quantitatively in vivo, but interobserver reproducibility is questionable. It confirms the tendinous elastographic anisotropy and stiffness augmentation of stretched tendon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
128
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(156 citation statements)
references
References 34 publications
22
128
4
Order By: Relevance
“…This result is in accordance with several previous studies who have found no correlation of shear modulus with physiological parameters (Aubry et al, 2013;Gennisson et al, 2005;Debernard et al, 2011), altough correlations were observed between BMI and trapezius muscle stiffness (Kuo et al, 2013) or with biceps brachii and biceps femoris muscles stiffness (Berko et al, 2013). However, muscle shear modulus depends on a large number of parameters, the study of a small specific and heterogeneous sample does not suffice to evaluate correlations; a large scale study have to be considered.…”
Section: Discussionsupporting
confidence: 77%
“…This result is in accordance with several previous studies who have found no correlation of shear modulus with physiological parameters (Aubry et al, 2013;Gennisson et al, 2005;Debernard et al, 2011), altough correlations were observed between BMI and trapezius muscle stiffness (Kuo et al, 2013) or with biceps brachii and biceps femoris muscles stiffness (Berko et al, 2013). However, muscle shear modulus depends on a large number of parameters, the study of a small specific and heterogeneous sample does not suffice to evaluate correlations; a large scale study have to be considered.…”
Section: Discussionsupporting
confidence: 77%
“…In an echo-time study on 80 healthy individuals, Aubry and collaborators (40) confirmed that Achilles tendon stiffness increases with stretching and that c s values are higher when measured parallel (along the long axis) to the tendon fibers, as opposed to perpendicular (along the short axis), as a result of tendon anisotropy. To summarize, shear waves propagate faster in stiffer and contracted tissues and along the long axis of the tendon.…”
Section: Figure 1 (A)mentioning
confidence: 90%
“…By estimating the shear wave time of flight, shear wave velocities of a15 m/s and a5 m/s were measured parallel and perpendicular to the fiber orientation respectively. Given these values and the frequency range used for the SSI technique (300 -800 Hz), the shear wave wavelengths are greater than the mean tendon thickness (a 4 mm) [3]. Thus, shear waves may be guided along and across the tendon as Lamb waves as it has already been observed in cornea [4] and arteries [5].…”
Section: Introductionmentioning
confidence: 94%
“…In [2] Young's modulus of 134 kPa and 35 kPa were obtained parallel and perpendicular to the fiber orientation respectively. Recently, Aubry et al [3] evidenced anisotropy by applying the Supersonic Shear Imaging (SSI) technique in vivo to human Achilles tendons. By estimating the shear wave time of flight, shear wave velocities of a15 m/s and a5 m/s were measured parallel and perpendicular to the fiber orientation respectively.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation